The Correlation between Sputum Retention and Oxygen Saturation in Nasopharyngeal Cancer Patients with Tracheostomy at The Emergency Department of Dharmais Cancer Hospital in 2022 - Repidawati Sinaga; Yuni Susilowati; Meynur Rohmah; Bernardo Oliber A. Arde (Jurnal Ilmiah Kesehatan, 2023)
The Global Burden of Cancer Study (Globocan) stated that nasopharyngeal cancer is the fifth most common cancer in Indonesia, with an incidence of 19,943 cases. One of the therapies for patients with nasopharyngeal cancer is a tracheostomy. Post-tracheostomy care is critical because blockage in the cannula due to accumulation of secretions impact decreasing oxygen saturation and result in death. This study analyzes the correlation between sputum retention and oxygen saturation in nasopharyngeal cancer patients with tracheostomy at the Emergency Department of Dharmais Cancer Hospital in 2022. It was correlational quantitative research with a cross-sectional approach. The study population was all nasopharyngeal cancer patients with tracheostomy at the Emergency Department, Dharmais Cancer Hospital, from August to November 2022, totaling 65 respondents. There were 65 respondents with a total sampling technique. The data collection used secondary data, namely the level of sputum retention and oxygen saturation in nasopharyngeal cancer patients with tracheostomy. Data analysis was univariate analysis and bivariate analysis through chi-square test. The result showed that most respondents experienced poor sputum retention (61.5%) and moderate hypoxemia (63.1%). The chi-square test obtained a p=0.000 (p<0.05). Thus, there was a correlation between sputum retention and oxygen saturation in respondents. In conclusion, sputum retention correlates with oxygen saturation in nasopharyngeal cancer patients with tracheostomy at the Emergency Department of Dharmais Cancer Hospital. The hospital should continue improving the ability of nurses to manage airway blockage through regular training.